Man and boy - Parsons, Tony, 1953- (London : Harper, 2008)
Thirty-year-old Harry struggles to adjust to life as an unemployed single dad when he loses his wife and his high-paying media job after a one-night stand with a female associate.
Adult.
Adult
Keywords: Adult children of aging parents -- Fiction; Boys -- Fiction; Fathers and sons -- Fiction; Motherless families -- Fiction; World War, 1914-1918 -- Veterans -- Fiction; Adult children of aging parents -- Fiction; Boys -- Fiction; Domestic fiction; Father-son relationship -- Fiction; Motherless families -- Fiction; Veterans -- Fiction; World War, 1914-1918 -- Fiction; Domestic fiction